A Rare Case of Aplastic Anemia in Toxic Typhoid Fever - Novita, Mutiara Putri; Zaimatuddunia, Irma (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Typhoid fever is a prevalent febrile illness in tropical regions where public health infrastructure and sanitation are limited. Pancytopenia resulting from hemophagocytic lymphohistiocytosis (HLH) is a rare but severe complication of typhoid fever that can be fatal without proper management. Objective: This case report aims to describe the clinical presentation, management, and outcome of a typhoid fever patient who developed pancytopenia, altered consciousness, and speech impairment. Methods: A comprehensive evaluation was conducted, including the patient’s medical history, physical examination, and various diagnostic tests. Laboratory workups revealed pancytopenia, positive TUBEX IgM for Salmonella, lymphadenopathy, and bone marrow aplasia. Differential diagnoses were considered and ruled out to confirm HLH as the underlying mechanism. Results: The patient responded positively to a regimen including ceftriaxone, steroids, and supportive care. The presence of pancytopenia in this typhoid fever case was linked to HLH. Conclusion: Early diagnosis and appropriate antibiotic therapy are critical for managing severe typhoid fever cases with complications such as HLH, helping prevent further complications and improving patient outcomes.